2014
DOI: 10.1186/1742-9994-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Goats excel at learning and remembering a highly novel cognitive task

Abstract: IntroductionThe computational demands of sociality (maintaining group cohesion, reducing conflict) and ecological problems (extractive foraging, memorizing resource locations) are the main drivers proposed to explain the evolution cognition. Different predictions follow, about whether animals would preferentially learn new tasks socially or not, but the prevalent view today is that intelligent species should excel at social learning. However, the predictions were originally used to explain primate cognition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 79 publications
2
61
0
1
Order By: Relevance
“…They also have good visual discrimination learning abilities (e.g. Langbein, Nürnberg, & Manteuffel, 2004) and long-term memory (Briefer, Haque, Baciadonna, & McElligott, 2014;Briefer, Padilla de la Torre, & McElligott, 2012). The most common goat vocalization is the contact call, which is used to maintain contact at relatively close distance (Briefer & McElligott, 2011a).…”
mentioning
confidence: 99%
“…They also have good visual discrimination learning abilities (e.g. Langbein, Nürnberg, & Manteuffel, 2004) and long-term memory (Briefer, Haque, Baciadonna, & McElligott, 2014;Briefer, Padilla de la Torre, & McElligott, 2012). The most common goat vocalization is the contact call, which is used to maintain contact at relatively close distance (Briefer & McElligott, 2011a).…”
mentioning
confidence: 99%
“…Yet, as group size increases, so too does the number of potential competitors, which increases the frequency of social monitoring (Favreau et al, 2010). However, the ability of goats, and other social herbivores, to keep track of when every herd member started to feed (and thus estimate finder"s share) may be limited by their cognitive ability, despite the noted intelligence of goats (Briefer, Padilla de la Torre, & McElligott, 2012;Briefer, Haque, Baciadonna, & McElligott, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in cattle and pigs have shown that body height and/or general facial features can be sufficient for discrimination between humans (Koba and Tanida, 2001;Rybarczyk et al, 2001), and it is likely that the discrimination process in goats might operate in a similar manner (see Keil et al, 2012). In relation to potential long term recognition of humans, good memory capacities over several modalities can be presumed in this species, as research on mother-offspring recognition and problem-solving has shown (Briefer et al, 2014(Briefer et al, , 2012. When goats learned how to solve a 2-step puzzle box in order to receive a reward, they were able to memorize this association for several months (Briefer et al, 2014).…”
Section: Discrimination Between and Attributing Attention To Humansmentioning
confidence: 99%
“…In relation to potential long term recognition of humans, good memory capacities over several modalities can be presumed in this species, as research on mother-offspring recognition and problem-solving has shown (Briefer et al, 2014(Briefer et al, , 2012. When goats learned how to solve a 2-step puzzle box in order to receive a reward, they were able to memorize this association for several months (Briefer et al, 2014). It is quite likely that learning processes associated with humans (e.g.…”
Section: Discrimination Between and Attributing Attention To Humansmentioning
confidence: 99%